The Influence of Basaltic Islands on the Oceanic REE Distribution: A Case Study From the Tropical South Pacific - Molina-Kescher, Mario; Hathorne, Ed C.; Osborne, Anne H.; Behrens, Melanie K.; Kölling, Martin; Pahnke, Katharina; Frank, Martin (Frontiers in Marine Science, 2018)
The Rare Earth Elements (REEs) have been widely used to investigate marine biogeochemical processes as well as the sources and mixing of water masses. However, there are still important uncertainties about the global aqueous REE cycle with respect to the contributions of highly reactive basaltic minerals originating from volcanic islands and the role of Submarine Groundwater Discharge (SGD). Here we present dissolved REE concentrations obtained from waters at the island-ocean interface (including SGD, river, lagoon and coastal waters) from the island of Tahiti and from three detailed open ocean profiles on the Manihiki Plateau (including neodymium (Nd) isotope compositions), which are located in ocean currents downstream of Tahiti. Tahitian fresh waters have highly variable REE concentrations that likely result from variable water–rock interaction and removal by secondary minerals. In contrast to studies on other islands, the SGD samples do not exhibit elevated REE concentrations but have distinctive REE distributions and Y/Ho ratios. The basaltic Tahitian rocks impart a REE pattern to the waters characterized by a middle REE enrichment, with a peak at europium similar to groundwaters and coastal waters of other volcanic islands in the Pacific. However, the basaltic island REE characteristics (with the exception of elevated Y/Ho ratios) are lost during transport to the Manihiki Plateau within surface waters that also exhibit highly radiogenic Nd isotope signatures. Our new data demonstrate that REE concentrations are enriched in Tahitian coastal water, but without multidimensional sampling, basaltic island Nd flux estimates range over orders of magnitude from relatively small to globally significant. Antarctic Intermediate Water (AAIW) loses its characteristic Nd isotopic signature (-6 to-9) around the Manihiki Plateau as a consequence of mixing with South Equatorial Pacific Intermediate Water (SEqPIW), which shows more positive values (-1 to -2). However, an additional Nd input/exchange along the pathway of AAIW, eventually originating from the volcanic Society, Tuamotu and Tubuai Islands (including Tahiti), is indicated by an offset from the mixing array of AAIW and SEqPIW to more radiogenic Nd isotope compositions.